UPAYA MENINGKATKAN GERAK LOKOMOTOR LARI 40 METER MELALUI METODE PICTURE AND PICTURE KELAS IIA SDS KRISTEN KANAAN KUBU RAYA - Riyanto, Sigit (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract Problem of the research is how the picture and picture method can increase the learning outcomes locomotor movement in 40 metres run to students grade IIA SDS Kristen Kanaan Kubu Raya Regency. The purpose of this research is to know the effort increasing locomotor movement in 40 metres run through picture and picture method to students grade IIA SDS Kristen Kanaan Kubu Raya Regency. Research methodology is Descriptive method with Classroom Action Research. Subject of the research was 23 student grade IIA from elementary school. Technique of data analysis was percentage achieved mastery. The result of the research can be concluded that learning with picture and picture method can increase the learning outcomes of locomotor movement in running about 40 metres in every single action given. Before treatment given, the mastery of the students was only 4,35%, then in cycle 1 increases become 39,13%, after treatment given cycle 2 the learning increases become 78,26%. Keywords: Picture and Picture, Locomotor, 40 Metres Run. Â